History and Current State of Tatar Language Teaching in the Republic Of Tatarstan - Khanova, Zulfiya Gabdelbarovna; Kirillova, Zoya Nikolaevna; Alkaya, Ercan (Rml Consultores, 2017)
This work is devoted to a research of history and the current state of teaching Tatar and consists of the following parts: historical digression to the 16-19th centuries and the review of activities for teaching Tatar in Tatarstan since the 20-30th years of the 20th century before the beginning of the 21st century. In a research the following methods were used: descriptions, observations, analysis of documents, induction, comparative method etc. The Tatar rich with ancient literary traditions played a role of the second state language in the 17-18th centuries and in the first half of the 19th century in domestic policy of Russia and in diplomatic relations with the countries of the East, and it was taught not only in Kazan, but also in educational institutions of many cities of Russia. Tatar for the first time in the history was announced by an official state language on an equal basis with Russian only in 1921. At this time within realization of new language policy mass training in Tatar began. In the 1920-1930th years a great job on teaching Tatar in various educational institutions of the republic was done. After a long break in 1992 there was a repeated giving to Tatar of the status of a state language that led to development of national education which is continued and today.
Keywords: Tatar; teaching Tatar; teaching history; Republic of Tatarstan; educational institutions; courses; circles